Investigation of adsorption characteristics of N,N'-[(methylimino)dimethylidyne]di-2,4-xylidine as corrosion inhibitor at mild steel/sulphuric acid interface - Singh A.K.; Shukla S.K.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
The corrosion inhibition properties of N,N'-[(methylimino)dimethylidyne]di-2,4-xylidine (MIDX) for mild steel corrosion in 0.5M H 2SO 4 solution was studied using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and gravimetric methods. These results were supplemented by atomic force microscopy (AFM) and scanning electron microscopy (SEM). Mixed mode of adsorption (physisorption as well as chemisorption to some extent) is proposed for the inhibition and the process followed the Langmuir adsorption isotherm and kinetic/thermodynamic model of El-Awady et al. Potentiodynamic polarization study clearly revealed that MIDX acted as mixed type inhibitor. The experimental data showed a frequency distribution and therefore a modelling element with frequency dispersion behaviour and a constant phase element (CPE) have been used. The results obtained from the different corrosion evaluation techniques are in good agreement. © 2011 Taiwan Institute of Chemical Engineers.